Manajemen Pembiayaan Pendidikan Masa Pandemi Covid 19 di SMP Negeri 1 Ciamis - Darmiasih, Dedeh; Sintawati, Anita; Herlinawati, Elin (Journal of Management Review, 2024)
The Covid-19 pandemic is an international disaster that has shaken all aspects of life, including the world of education. So that it also has an impact on the management of education financing in schools. In response to this, the government has taken a policy regarding the flexibility in the use of School Operational Assistance (BOS) funds for educational institutions to use for essential needs to be met. Based on this, the researchers conducted research on the management of education financing at SMP Negeri 1 Ciamis. The purpose of this study was to determine the management of education financing at SMP Negeri 1 Ciamis during the Covid 19 pandemic. This study used a qualitative descriptive approach by examining the facts that occurred. Financing management at SMP Negeri 1 Ciamis includes planning, management, implementation and supervision, focusing on the needs of schools, teachers and students. The Covid-19 pandemic has had an impact on activities that have been budgeted for from BOS funds, such as competition activities being reduced because the funds are to meet the purchase of medical equipment that must be provided in schools.